A Thematic Study of Moral Education in Surah An-Nur Verses 27–31: An Analysis of Ibn Kathir’s Tafsir and Tafsir Al-Misbah - Siti Nurhayati; Benny Prasetiya; Muhammad Alfi Syahrin; Khamam Khosiin (PT. Caesarindo Triloka Persada, 2026)
This study aims to examine the moral education values contained in Surah An-Nur verses 27-31 and their relevance within the context of contemporary Islamic education. The research adopts a qualitative approach through a library research design. The primary data sources consist of the Qur’an, specifically Surah An-Nur verses 27-31, as well as Ibn Kathir’s Tafsir and Tafsir Al-Misbah, while secondary data are obtained from Islamic education literature and related studies. Data were collected through documentation techniques and analysed using descriptive-analytical and comparative methods by examining the similarities and differences in the interpretations of the two exegetes. The findings indicate that Surah An-Nur verses 27-31 contain moral education values, including visiting etiquette, respect for privacy, control of the gaze (ghadd al-bashar), and the preservation of personal dignity (hifzh al-farj). The exegetical analysis shows that Ibn Kathir emphasises normative aspects and adherence to Islamic law, whereas Tafsir Al-Misbah presents a contextual and persuasive approach. The integration of these two perspectives affirms that Qur’anic moral education is comprehensive, dynamic, and relevant for character formation in the modern era.